Regulation of Sexually Dimorphic Expression of Major Urinary Proteins - Penn, Dustin J.; Zala, Sarah M.; Luzynski, Kenneth C. (Frontiers in Physiology, 2022)
Male house mice excrete large amounts of protein in their urinary scent-marks, mainly composed of Major Urinary Proteins (MUPs), and these lipocalins function as pheromones and pheromone-carriers. Here, we review studies on sexually dimorphic MUP expression in house mice, including the proximate mechanisms controlling MUP gene expression and their adaptive functions. Males excrete 2 to 8 times more urinary protein than females, though there is enormous variation in gene expression across loci in both sexes. MUP expression is dynamically regulated depending upon a variety of factors. Males regulate MUP expression according to social status, whereas females do not, and males regulate expression depending upon health and condition. Male-biased MUP expression is regulated by pituitary secretion of growth hormone (GH), which binds receptors in the liver, activating the JAK2-STAT5 signalling pathway, chromatin accessibility, and MUP gene transcription. Pulsatile male GH secretion is feminized by several factors, including caloric restriction, microbiota depletion, and aging, which helps explain condition-dependent MUP expression. If MUP production has sex-specific fitness optima, then this should generate sexual antagonism over allelic expression (intra-locus sexual conflict) selectively favoring sexually dimorphic expression. MUPs influence the sexual attractiveness of male urinary odor and increased urinary protein excretion is correlated with the reproductive success of males but not females. This finding could explain the selective maintainence of sexually dimorphic MUP expression. Producing MUPs entails energetic costs, but increased excretion may reduce the net energetic costs and predation risks from male scent marking as well as prolong the release of chemical signals. MUPs may also provide physiological benefits, including regulating metabolic rate and toxin removal, which may have sex-specific effects on survival. A phylogenetic analysis on the origins of male-biased MUP gene expression in Mus musculus suggests that this sexual dimorphism evolved by increasing male MUP expression rather than reducing female expression.